Beauveria bassiana em associação com milho geneticamente modificado no manejo de Spodoptera frugiperda e Rhopalosiphum maidis - Moraes, Renato Franco Oliveira De; Toscano, Luciana Cláudia; Pereira, Marcelo Francisco Arantes; Pietrobom, Valter Luis; Barboza, Cecília Aparecida Moreira Dos Santos; Maruyama, Wilson Itamar (Instituto Biológico, 2015)
ABSTRACT: The objective of this study work was to evaluate the efficiency of the fungusBeauveria bassiana (isolate CG 716) to controlSpoodptera frugiperda and Rhopalosiphum maidis on maize. Front this, was set up in randomized blocks split plots design, with 10 treatments and four replications. Treatments were applied to plots: B. bassiana formulated in vegetable oil at doses of 2.0, 4.0 and 6.0 x 1012 conidia ha-1, lambda-cyhalothrin (7.5 a.i. ha-1) and control (no application). Applications were made weekly. Assessments were performed before each application of the products, collecting 10 consecutive plants per plot for subsequent and storing in plastic bag from destruction of the whorl of maize and counting the number of fall armyworm larvae, aphids and natural enemies in laboratory. There were no significant differences among treatments in relation to the population ofS. frugiperda larvae and R. maidis in corn fields treated or not treated with of defensives applications, however, higher number of R. maidis was observed on the conventional cultivar at 40 days after emergence (DAE) treated with the bioinsecticide B. bassiana at a dose of 2.0 x 1012 conidia ha-1. B. bassiana associated withBt technology does not show satisfactory results to controlS. frugiperda .

RESUMO: O objetivo deste trabalho foi avaliar a eficiência do fungo Beauveria bassiana (isolado CG 716) no manejo de Spodoptera frugiperda e Rhopalosiphum maidis em milho. Diante disso, montou-se um experimento em blocos ao acaso, utilizando parcelas subdivididas, contendo dez tratamentos e quatro repetições. Os tratamentos foram: B. bassiana , formulado em óleo vegetal, nas doses de 2,0, 4,0 e 6,0 x 1012 conídios ha-1, lambda-cialotrina (7,5 i.a. ha-1) e testemunha (sem aplicação). As aplicações foram realizadas a partir dos 10 dias após a emergência (DAE) das plantas, sendo repetidas aos 16, 23 e 31 DAE. As avaliações foram realizadas semanalmente coletando-se dez plantas consecutivas por parcela e armazenadas em sacos plásticos, para posterior destruição do cartucho e contagem de lagartas, pulgões e inimigos naturais em laboratório. Não ocorreram diferenças significativas em populações de S. frugiperda e R .maidis em lavouras de milho submetidas ou não a aplicações de defensivos; entretanto, na variedade convencional, aos 40 DAE, foi constatado que um maior número médio pulgõessob aplicação do bioinseticida na dosagem de 2,0 x 1012 conídios ha-1. B. bassiana ,em associação com a tecnologia Bt , não produziu resultados satisfatórios no controle de S. frugiperda e R. maidis nas condições em que foi testado.
Beauveria bassiana in association with genetically modified maize on Spodoptera frugiperda and Rhopalosiphum maidis management
Keywords: armyworms; entomopathogenic fungis; aphid corn; Zea mays; transgenics; lagarta-do-cartucho; fungo entomopatogênicos; pulgão-do-milho; Zea mays; transgênicos